분리 대동맥판막하 협착증 수술의 임상적 고찰 - 유송현; 임상현; 홍유선; 박영환; 장병철; 강면식; Yu Song Hyeon; Lim Sang Hyun; Hong You Sun; Park Young Hwan; Chang Byung Chul; Kang Meyun Shick (Taehan Hyungbu Oekwa Hakhoe chi, 2005)
Background: Discrete subaortic stenosis is known to recur frequently even after surgical resection. We retrospectively reviewed the preoperative and postoperative changes in pressure gradient through left ventricular outflow tract, and the recurrence rate. Material and Method: Between September 1984 and December 2004, 34 patients underwent surgical treatment. Mean age of patients was $17.1±15.2$ years and 19 patients $(55.9%)$ were male, 16 patients $(47.1%)$ had previous operations and associated diseases were aortic regurgitation (11), coarctation of aorta (3), and others. Result: Immediate postoperative peak pressure gradient was significantly lower than preoperative peak pressure gradient (21.8 mmHg vs 75.8 mmHg, p<0.04). Peak pressure gradient measured after 50.3 months of follow up was 20.2 mmHg which was also significantly lower than that of preoperative value but not significantly different from that of immediate postoperative value. There was no surgical mortality but one patient developed cerebral infarction. Mean follow up duration was $69.8±54.6\;months$. During this period, 5 patients $(14.7%)$ had reoperation, 3 $(8.8%)$ of whom were due to recurred subaortic stenosis. We found no risk factors for recurrence and survival for free from reoperation was $76.4%$. Conclusion: Excision of subaortic membrane combined with or without myectomy in discrete subaortic stenosis showed sufficient relief of left ventricular outflow tract obstruction with low mortality and morbidity, but careful long term follow up is necessary for recurrence, since it is not predictable. 배경: 분리 대동맥판막하 협착증은 수술 후에도 재발을 잘하는 것으로 알려져 있다 저자들은 수술 전후의 좌심실 유출로를 통한 압력차 및 재발률 등에 대하여 후향적 연구를 시행하였다 대상 및 방법: 1984년 9월부터 2004년 12월까지 34명의 환자가 분리 대동맥판막하 협착증으로 수술을 시행 받았다. 평균 나이는 $17.1±15.2$세였으며 19명$(55.9%)$이 남자였다. 16명$(47.1%)$의 환자가 이전에 심장수술을 받았다. 수술시 동반된 질환은 대동맥판막 폐쇄부전(11), 대동맥 축착증(3) 등이었다. 걸U: 수술직후의 좌심실 유출로를 통한 최대 압력차는 수술 전보다 유의하게 낮았고(75.8 mmHg vs 21.8mmHg, p<0.01), 평균 50.3개월 후에 측정된 치대 압력차도 20.2 mmHg로 수술 직후와 큰 차이 없이 여전히 수술 전보다 낮은 수치를 나타내었다. 수술 사망은 없었으며 1예에서 수술 후 합병증으로 뇌경색이 발생하였다. 평균 추적 관찰 기간은 $69.8±54.6$개월이었으며, 이 기간 중에 5명$(14.7%)$이 재수술을 시행 받았고, 이 중 3명$(8.8%)$의 환자는 분리 대동맥판막하 협착의 재발로 인해 재수술을 시행 받았다. 통계적으로 유의한, 재발에 대한 위험인자는 없었으며 10년에서의 무재수술 생존율은 $76.4%$였다. 결론: 분리 대동맥판막하 협착증의 치료에 있어 대동맥판막하 막성 조직만을 제거하거나 혹은 주위 근육과 함께 절제하는 방법은 낮은 사망률과 합병증을 보였으며 수술 후 충분한 좌심실 유출로 최대압력차의 감소를 보였다. 그러나 재발을 잘하고 예측할만한 위험 인자가 없으므로 지속적인 추적 관찰이 필요하리라 생각한다.